OPTIMALISASI PROSES ADMINISTRASI PENGOPERASIAN PESAWAT N219 UNTUK MENINGKATKAN KESELAMATAN DAN KELAIKAN UDARA - Ari Sigit; Mursyid, Mursyid (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2025)
The administrative process which includes licensing, recording, reporting and supervision must run smoothly so that aircraft operations can take place without bureaucratic obstacles. Poor or inefficient administration can result in delays, increased operational costs, and potential undesirable safety risks. The aim of this research is to determine the optimization of the administration process for operating the N219 aircraft to improve safety and airworthiness. Data analysis was carried out using the triangulation method, including data reduction, data presentation and verification/conclusion. Optimizing the administration process for operating the N219 aircraft is a must. This is because the optimization process includes several important things to improve safety and airworthiness, such as certification development, certification production, aircraft registration, air operator certification, crew training licenses, operational arrangements, maintenance inspections and legal insurance.